Electronic Monitoring in Europe – a Panacea for Reforming Criminal Sanctions Systems? A Critical Review - Dünkel, Frieder (Kriminologijos studijos, 2018)
[full article, abstract in English; abstract in Lithuanian] First experiments with electronic monitoring emerged in Europe in the early 1990s. Within 15 years, the majority of countries in Europe reported having introduced electronic monitoring at least as pilot projects. The amazing dynamic rise of electronic monitoring in Europe may be explained by the commercial interests that become evident when looking at the activities of private companies selling the technique. Although electronic monitoring seems to have expanded in many countries, one has to realize its marginal role within the European sanctions systems compared to other sentencing or release options. On average, only about 3% of all probationary supervised persons were under electronic monitoring at the end of 2013. This article deals with questions regarding the impact of electronic monitoring on prison population rates and reduced reoffending, with net-widening effects and costs, essential rehabilitative support, human rights-based perspectives and the general (non)sense of electronic monitoring.